Pesan Moral dalam Tayangan Film Pendek “Jagat Raya 2” di Youtube - Septiningsih, Ridha; Yuwono, Andri Prasetyo (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This research investigates the moral message conveyed by the movie “Jagat Raya 2” through a qualitative approach. This research uses Ferdinand De Saussure's semiotic analysis, which includes signifier and signified. This movie is valued because it has a moral message. This short film tells the story of a teaching concept that is beneficial for teachers and students in the classroom with progressive education theory. This movie is a product of the Merdeka Belajar era and is used as an alternative to methods. Through documentation and observation of this movie, which is divided into scenes, several moral messages about life are found. One of them is to provide space for students to determine attitudes towards their own choices while teachers can provide differentiated learning while providing a stimulus that can move students in building human resources. Through film media, it is hoped that this character education can be implemented as the goal of the Merdeka Belajar program and create quality education.